Relationships between Urban Form and Travel Behaviour in Athens, Greece. A Comparison with Western European and North American Results - Dimitris Milakis; Thanos Vlastos; Nikos Barbopoulos (European Journal of Transport and Infrastructure Research, 2008)
In Athens, a series of political events during the last two centuries influenced urban planning, resulting in a unique land use and transport system. In this paper, we examine their relationships in this uncommon system and compare them with those in Western European and North American cities. Data from Metro Development Study (1996) were employed in multiple regression models for Athens, while results from similar studies in Western cities were used as the basis for comparisons. The results for Athens show that residential density is a key factor influencing mainly modal split, whereas distance from city centre and the extent of road network mainly influence trip length and energy consumption by car. An interesting threshold of 200 persons/ha is identified, in which significant changes in travel behaviour occur. In contrast, “land use mix” appeared to have no effects on travel behaviour. The international comparisons revealed differences regarding the density threshold and the role of land use mix, while results concerning residential density, distance from city centre and socio-economic characteristics are in line with those from other European and American cities. The case of Athens adds to the notion that land use policies could constitute a tool for changing travel behaviour. However, urban form parameters, and their critical thresholds, may vary from country to country, especially among cities in Europe and America, which means that no universal standards can be adopted. Finally, it could be argued that in all cases, if more compact urban structures are adopted, more sustainable travel patterns will emerge.